Implementasi Pengujian Otomatis End-To-End Menggunakan Cypress dengan Metode Black Box Testing untuk Meningkatkan Kualitas Aplikasi EdTech XYZ Berbasis Website - Rina Septiani; Budi Jejen Zaenal Abidin; Angge Firizkiansah (JIKOMTI : Jurnal Ilmiah Ilmu Komputer dan Teknologi Informasi, 2025)
Software quality is an important aspect of development because it affects user satisfaction. Therefore, testing is necessary to ensure that the software runs according to specifications and minimizes errors. However, manual testing tends to be time-consuming, resource-intensive, and prone to human error. This study focuses on improving software quality through the implementation of end-to-end automated testing using Cypress with the black box testing method and following the Software Testing Life Cycle (STLC) stages. The test results show that all test cases were successfully executed with a pass status after improvements were made to the program code, which means that the application is functioning according to specifications. Thus, automated testing has proven to be effective and efficient in improving application quality. Further research is recommended to integrate Cypress with the CI/CD pipeline to support continuous testing automation.